Dionysos in classical Athens : an understanding through images - Isler-Kerényi, Cornelia. (Religions in the Graeco-Roman World, 2015)
Dionysos, with his following of satyrs and women, was a major theme in a big part of the figure painted pottery in 500-300 B.C. Athens. As an original testimonial of their time, the imagery on these vases convey what this god meant to his worshippers. It becomes clear that - contrary to what is usually assumed - he was not only appropriate for wine, wine indulgence, ecstasy and theatre. Rather, he was present in both the public and private sphere on many, both happy and sad, occasions. In addition, the vase painters have emphasized different aspects of Dionysos for their customers inside and outside of Athens, depending on the political and cultural situation.